Status of subclinical mastitis in lactating cows of selected dairy farms in Bangladesh and farmers’ understanding of mastitis - Amit Kumar Dey; Chaiti Dhali; Sompa Das; Sukanta Chowdhury (Microbes, Infection and Chemotherapy, 2023)
Background: Subclinical mastitis, a disease that is economically important to dairy cows, affects milk production. Management of udder health is an essential element in the process of safe milk production. Consumption of milk with a high somatic cell count (SCC) may also pose a health risk to humans. Objectives. We aimed to evaluate the SCC method for the detection of SCM in dairy cows and to assess farmers’ knowledge, attitudes, and practices towards mastitis detection and control. Methods. A cross-sectional study was conducted to evaluate the current status of subclinical mastitis (SCM) in lactating dairy cows. The research work was also designed to assess farmers’ knowledge, attitudes, and practices about bovine mastitis. A total of 320 milk samples from 80 lactating cows were collected for physical examination and tested for subclinical mastitis using SCC. Results. Out of 80 lactating cows examined, 53 (66%, 95% CI: 55-76%) cows were diagnosed with subclinical mastitis. The average cow level SCC per ml of milk was 503101. According to the farmers’ self-report, 100% of farms practiced hand milking and 100% of milkmen washed their hands before milking. The majority of farms (90%) had brick floors. Most of the farmers (70%) knew about screening for subclinical mastitis. However, they never performed screening to detect subclinical mastitis. Conclusion. The high prevalence of SCM in dairy raised significant concerns about farm management, personal hygiene and biosecurity practices. Further study is needed to identify the etiologies of SCM and its associated risk factors.